Hepatocyte Growth Factor-Induced Tendon Stem Cell Conditioned Medium Promotes Healing of Injured Achilles Tendon - Zhang, Zenan; Li, Yutian; Zhang, Tingting; Shi, Manyu; Song, Xin; Yang, Shulong; Liu, Hengchen; Zhang, Mingzhao; Cui, Qingbo; Li, Zhaozhu (Frontiers in Cell and Developmental Biology, 2021)
Tendon repair is a medical challenge. The present study investigated the effectiveness of acellular therapy consisting of conditioned medium (CM) of tendon stem cells (TSCs) induced with hepatocyte growth factor (HGF) in promoting the healing of injured Achilles tendon in a rat model. Proteomic analysis of soluble substances in the CM was performed using an array chip, and bioinformatic analysis was carried out to evaluate interactions among the factors. The effects of CM on viability and migratory capacity of tendon fibroblasts derived from rats with ruptured Achilles tendon were evaluated with the Cell Counting Kit 8 and wound healing assays, respectively. The expression of extracellular matrix (ECM)-related proteins was assessed by western blotting. Rats with Achilles tendon injury were treated with CM by local injection for 2 weeks, and the organization of tendon fibers at the lesion site was evaluated by hematoxylin and eosin and Masson’s trichrome staining of tissue samples. The deposition and degradation of ECM proteins and the expression of inflammatory factors at the lesion site were evaluated by immunohistochemistry and immunofluorescence. Biomechanical testing was carried out on the injured tendons to assess functional recovery. There were 12 bioactive molecules in the CM, with HGF as the hub of the protein–protein interaction network. CM treatment enhanced the viability and migration of tendon fibroblasts, altered the expression of ECM proteins, promoted the organization of tendon fibers, suppressed inflammation and improved the biomechanics of the injured Achilles tendon. These results suggest that HGF stimulates the secretion of soluble secretory products by TSCs and CM promotes the repair and functional recovery of ruptured Achilles tendon. Thus, HGF-induced TSC CM has therapeutic potential for the treatment of tendinopathy.